1998
DOI: 10.1021/jp9824860
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic Tracer Studies of Propane Reactions on H−ZSM5 Zeolite

Abstract: Reactions of 13 C-labeled alkanes show that chain growth and cyclization reactions on H-ZSM5 require the initial formation of the corresponding alkene and its extensive participation in rapid oligomerization/ -scission reactions before cyclization occurs. The role of alkene intermediates was established by the initial formation of predominantly unlabeled products from mixtures of propene and propane-2-13 C reactants. Aromatic products of propane-2-13 C reactions on H-ZSM5 contain similar fractions of 13 C-atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
46
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 29 publications
14
46
0
1
Order By: Relevance
“…3b) results in a good description of the formation of butanes and has no noticeable effect on ethane formation. These results allow us to conclude that at low propane conversions over H-ZSM-5 ethane is formed in the HT steps involving propane and adsorbed ethene molecules, and not in the steps of ethene hydrogenation, as was assumed earlier by Biscardi and Iglesia (1998) and . Also, based on the data shown in Figs.…”
Section: Reaction Stepsupporting
confidence: 72%
See 2 more Smart Citations
“…3b) results in a good description of the formation of butanes and has no noticeable effect on ethane formation. These results allow us to conclude that at low propane conversions over H-ZSM-5 ethane is formed in the HT steps involving propane and adsorbed ethene molecules, and not in the steps of ethene hydrogenation, as was assumed earlier by Biscardi and Iglesia (1998) and . Also, based on the data shown in Figs.…”
Section: Reaction Stepsupporting
confidence: 72%
“…In fact, Price et al (1998) have shown that C 5 and C 6+ alkanes are not normally observed in the reaction mixture, or observed in very small concentrations because of their fast cracking into lower alkanes and alkenes. Furthermore, alkenes, once formed in the PC steps, participate in the fast oligomerization-cracking steps that control alkene distribution during alkane aromatization process (Biscardi and Iglesia, 1998;Haag, 1984;Lukyanov et al, 1995).…”
Section: Alkene Oligomerization-cracking Over Zeolite Acid Sites (10 mentioning
confidence: 99%
See 1 more Smart Citation
“…NH 4 -ZSM5 was treated in ambient air at 398 K overnight and then at 773 K in flowing dry air (Airgas, zero grade) for 20 h to form H-ZSM5. The synthesis and characterization of the H-ZSM5 samples have been reported elsewhere [17][18][19].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Then, subsequent alkene oligomerization and cracking, and finally main aromatics such as benzene, toluene and xylenes (BTX) were formed through a sequence of cyclization and hydride transfer steps including diene formation from hydride transfer of alkenes, cyclization of dienes and hydride transfer of cyclodienes [36,40,41]. The reaction rate is generally considered as an order of alkene oligomerization and cracking [ aromatization [ alkane dehydrogenation [42,43]. Nguyen et al [42] investigated the kinetic model of the reaction pathway of propane and n-butane aromatization over ZSM-5.…”
Section: Effect Of Synthesis Conditions To Para-selectivitymentioning
confidence: 99%